Commercialization and consumption of coffee in Mexico, a proposal of methodology approach - Marisol Velazquez (European Regional Science Association (ERSA), 2014)
This work presents advances of the doctoral thesis 'Commercialization and consumption of coffee in Mexico' under the governance approach proposed by Korzeniewicks (1994), Gereffi, Humphrey, Gereffi and Sturgeon (2005) and Ponte and Gibbon (2008). First, the paper discussed the theoretical framework of global value chains, from where it came and what is the history of art until today. The first version of governance refers to the domain of global value chains in a sense of control; the second has to do with coordination between suppliers and firms and; the third makes mention of the regulations, which means how much power have the rules, norms and standards in the domain of the chain. The methodology includes empirical studies of industrial goods, agri-food chains and coffee that were reviewed to locate indicators, similarities, differences and above all to establish relations of economic power that exist on each asset. In this sense, it emerged that several studies have used any of these approaches to assess the productive linkages, however, few used the three approaches to evaluate the same good or value chain. Thus, the proposal that is made in this paper is a methodology that incorporates the three meanings of governance in a single typology. In this way, it parses the string not only forward and backward, out or inside and towards, but workable, seen from a micro point of view, but also macro or global. Then, it shows the economic relationship between agents and its interaction with the economy in general. The objective of this work is to show the theoretical, methodological and a view of empirical advances of the GVC applying to the coffee chain which is discussed under governance in its new version to generate a discuss about this propose. It should be noted that under these dimension is intended to show the socio-economic situation of the producers of coffee in Mexico and how is their relationship with the other participants in the chain, both nationally and globally. The results show that, indeed, the new advance in GVC methodology can be used to evaluate agrifood chains, specifically the coffee chains. In this way, it parses the string not only forward and backward, out or inside and towards, but workable, seen from a micro point of view, but also macro or global. Then, it shows the economic relationship between agents and its interaction with the economy in general.
Keywords: 330; Global value chains; coffee; governance; Mexico